El impacto del desarrollo del café en un territorio no cafetalero: Conformación del municipio de mozos de Colotenango en Guatemala, 1877-1947 - Torras Conangla, Rosa (2005)
This article analyzes the way in which Colotenango, a mam territory in the impoverished Guatemalan highlands, became a part of the liberal economy in the nineteenth century by constituting a municipio de mozos for the coffee export plantations located in the coastal region. Since this land had traditionally been considered not apt for coffee-growing purposes, the governmental policy aimed at boosting the economy based on this product, had devastating effects on the municipalities of the indigenous highlands, such as the case of Colotenango. Particularly, this article delves into the role played by the Municipality in the agricultural export system, which became the essence of continuous jurisdictional conflicts in the region still present today.